SELEKSI PROJENI TANAMAN KARET (Hevea brasiliensis Muell. Arg.) DARI HASIL PERSILANGAN TAHUN 2001 – 2003 SEBAGAI PENGHASIL LATEKS DAN KAYU - Toni Akbar; Emmy Harso Kardhinata; eva Sartini Bayu; Sekar Woelan (Universitas Sumatera Utara, 2013)
The research has been done in ± 54 high sea level at Balai Penelitian Sungei Putih, Pusat PenelitianKaret, Galang, Deli Serdang-North Sumatera Province. The research held in February until July2012. The objective of this research to get the best progeny based on potential of latex yieldcharacteristic and timber yielding of crossing result 2001-2003. This research is done by measuringmean value, maximum value, minimum value, range, class, interval, correlation, 10% and 1%selection intensity. The research used to 1013 progeny on nine years old.Based on selection as latex with 10% selection intensity found 86 progeny, and 1% selectionintensity there are 34 progeny, and found 5 progeny can developed directly because haveproduction above 30 g/t/t. In hence, timber yielding progeny with 10% selection intensity there are132 progeny, and 1% selection intensity got 34 progeny. 15 progeny with 10% selected intensity aslatex and timber yielding namely: 13/01/A, 86/02/B, 41/01/A, 331/01/A, 57/01/A. 577/01/A,639/01/A. 45/02/B, 671/01/A, 239/01/A, 619/01/A, 160/01/A, 139/01/A, 195/01/A, and 423/01/Aand 1% selection intensity there are 3 progeny i.e. 139/01/A. 195/01/A, and 423/01/A.Key words : Hevea brasiliensis, hand pollination, selection, progeny.